Differential expression of phosphoinositide 3-kinase/protein kinase B and Toll-like receptor/nuclear factor kappa B signaling pathways in experimental obesity Wistar rat model - Song Liya; Li Lihua (Open Life Sciences)
This study investigated the effects of activation and inhibition of the PI3K/AKT and TLR-4/NF-κB signaling pathways on insulin resistance in a high-fat diet-induced obese rat model. The results indicate that a high-fat diet can activate these signaling pathways by regulating the expression of related proteins, affecting metabolic health. Rat PI3K/AKT pathway protein.